2020
DOI: 10.1371/journal.pntd.0008765
|View full text |Cite|
|
Sign up to set email alerts
|

Differential pathogenesis of Usutu virus isolates in mice

Abstract: Usutu virus (USUV; Flavivirus), a close phylogenetic and ecological relative of West Nile virus, is a zoonotic virus that can cause neuroinvasive disease in humans. USUV is maintained in an enzootic cycle between Culex mosquitoes and birds. Since the first isolation in 1959 in South Africa, USUV has spread throughout Africa and Europe. Reported human cases have increased over the last few decades, primarily in Europe, with symptoms ranging from mild febrile illness to severe neurological effects. In this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…In particular, neurovirulence was found to be increased in the Europe 2 lineage compared to the other lineages in one study 39 . Since these experiments were performed in the mouse model 28 , 39 , 58 on the one hand and under in-vitro conditions 39 on the other hand, the results should be interpreted cautiously in the context of the present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, neurovirulence was found to be increased in the Europe 2 lineage compared to the other lineages in one study 39 . Since these experiments were performed in the mouse model 28 , 39 , 58 on the one hand and under in-vitro conditions 39 on the other hand, the results should be interpreted cautiously in the context of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have shown that there are significant differences in the virulence of different lineages in both mouse models and in vitro cell culture experiments 28 , 39 , 58 . In particular, neurovirulence was found to be increased in the Europe 2 lineage compared to the other lineages in one study 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding USUV tissue and cell tropism, the same reports highlight the presence of the viral antigen in the major affected organs (liver, spleen, heart, brain) [ 5 , 21 , 22 , 23 ]. Despite the identification of different circulating virus lineages [ 17 ], studies investigating their pathogenetic potential in naturally-infected birds are lacking and it has only been partially studied in vitro and in experimental in vivo studies in mice [ 24 , 25 , 26 , 27 , 28 ]. Consequently, due to the small number of animals examined in previous studies, knowledge on the pathology and the complete cell and tissue tropism of the virus, as well as the pathogenetic potential of different circulating viral lineages, are still fragmentary.…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 ], and SAAR1776 (South Africa 1959, Africa 2 lineage, MN813492, passage 9, isolated from Culex neavei ) [ 3 ]. These strains have been previously sequenced by our lab [ 28 ].…”
Section: Methodsmentioning
confidence: 99%